Cellulose nanocrystal: A promising toughening agent for unsaturated polyester nanocomposite. (15th January 2015) - Kargarzadeh, Hanieh; M. Sheltami, Rasha; Ahmad, Ishak; Abdullah, Ibrahim; Dufresne, Alain
Abstract: New nanocomposites of an unsaturated polyester resin (UPR) and cellulose nanocrystals (CNCs) were prepared. Effects of CNC silane surface treatment on the morphology, mechanical and thermal properties, viscoelastic behavior and water absorption of CNC reinforced UPR have been studied. The results showed that the crystallinity index of the CNCs reduced after the surface treatment. However, it did not impact the size and aspect ratio of the rod-like nanoparticles. Tensile tests showed that both the strength and stiffness of the UPR improved upon the incorporation of silane treated CNCs (STCNCs), whereas no significant changes were observed on the impact energy after the treatment. Interestingly, the impact energy increased significantly with the addition of untreated CNCs. The viscoelastic behavior and thermal degradation for both the CNC and STCNC-reinforced nanocomposites were improved. The water-absorption behavior of the UPR was found to decrease upon incorporation of CNCs, and a further reduction was observed with STCNCs. Graphical abstract: Highlights: Unsaturated polyester resin was modified with cellulose nanocrystal. Cellulose nanocrystals were modified with silane coupling agent. Untreated cellulose nanocrystals improved impact properties significantly. Desirable properties were realized by both untreated and treated CNC contents.